Evaluation of the performance of the IFN-γ release assay in bovine tuberculosis free herds from five European countries - Alberto Gomez-Buendia; Beatriz Romero; Javier Bezos; José Luis Saez; Ivonne Archetti; Maria Lodovica Pacciarini; Maria Laura Boschiroli; Sébastien Girard; Emanuela Gutu; Florica Barbuceanu; Ourania Karaoulani; Athanasia Stournara; et al. (Veterinary Research, 2023)
Abstract The diagnostic methods for granting and maintenance of the official tuberculosis-free (OTF) status and for intra-Community movement of cattle are the tuberculin skin tests (single or comparative) and the interferon-γ (IFN-γ) release assay (IGRA). However, until now, IGRAs have been primarily applied in infected farms in parallel to the skin test to maximize the number of infected animals detected. Therefore, an evaluation of the performance of IGRAs in OTF herds to assess whether if their specificity is equal to or higher than that of the skin tests is needed. For this, a panel of 4365 plasma samples coming from 84 OTF herds in six European regions (five countries) was assembled and analysed using two IGRA kits, the ID Screen® Ruminant IFN-g (IDvet) and the Bovigam™ TB Kit (Bovigam). Results were evaluated using different cut-offs, and the impact of herd and animal-level factors on the probability of positivity was assessed using hierarchical Bayesian multivariable logistic regression models. The percentage of reactors ranged from 1.7 to 21.0% (IDvet: S/P ≥ 35%), and 2.1–26.3% (Bovigam: ODbovis–ODPBS ≥ 0.1 and ODbovis–ODavium ≥ 0.1) depending on the region, with Bovigam disclosing more reactors in all regions. The results suggest that specificity of IGRAs can be influenced by the production type, age and region of origin of the animals. Changes in the cut-offs could lead to specificity values above 98–99% in certain OTF populations, but no single cut-off yielding a sufficiently high specificity (equal or higher than that of skin tests) in all populations was identified. Therefore, an exploratory analysis of the baseline IFN-γ reactivity in OTF populations could help to assess the usefulness of this technique when applied for the purpose of maintaining OTF status.